Identification of Cation Elements in PM10 Concentration in Industrial Area of Penang (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
This study aims to investigate the concentrations of particulate matter with an aerodynamic diameter of less than 10 micron (PM10) and their associated cation elements in PM10. The sample of PM10 was collected at Royal Malaysian Customs Department (N5° 22’ 012”; E100° 23’589”) located in Perai Industrial Area, Penang, from June to September 2015. The sampling was carried out during the southwest monsoon and a total of 12 samples were collected using a low volume sampler (LVS). Results suggested that there are five elements that are commonly identified from PM sampled which are ammonium, sodium, potassium, calcium and magnesium. The concentrations of the cation from all four months in the industrial area shows the order of NH4 + > Ca+ > K+ > Mg2+ > Na+ . The lowest and highest concentrations calculated both were ammonium (0.012 ?g/m3) in July and (0.873 ?g/m3) September, respectively.
Keywords: Suspended Particulate Matter; Matter, Ion Chromatography; Low Volume Sampler